Enhancing Scrum Framework: a Case at a Multinational Manufacturing Company in Malaysia - Mariyappan, Shalini; Lee Abdullah, Nasuha; Idrus, Rosnah (International Journal of Engineering and Technology, 2018)
Many organizations today are adopting Scrum, an Agile methodology for handling complex software project. Despite all the benefits, there are still issues and challenges in adapting to Agile and some refusals to move from traditional method. This research aims to assess the perception of effectiveness of implementation of Scrum and identify the challenges after adopting Scrum in an information          technology (IT) department of company X, a multinational manufacturing company in Malaysia. The findings of this study revealed that after one year of adopting Scrum, the perceptions from the staff is there is no significant improvement made. Five challenges were    identified: team members unaware of each other’s tasks, difficulty in handling daily task priorities, no work synchronization among            management and delivery team, too many tasks at the middle of sprints and poor attendance during daily stand up meeting. An enhanced Scrum framework that uses Scrum and Kanban is proposed to address the identified challenges. The insights gained from this research hope to provide practitioners with useful reference for adopting scrum.